Vaccinia Virus A26 and A27 Proteins Form a Stable Complex Tethered to Mature Virions by Association with the A17 Transmembrane Protein - Howard, Amanda R. (American Society for Microbiology (ASM), 2008)
During vaccinia virus replication, mature virions (MVs) are wrapped with cellular membranes, transported to the periphery, and exported as extracellular virions (EVs) that mediate spread. The A26 protein is unusual in that it is present in MVs but not EVs. This distribution led to a proposal that A26 negatively regulates wrapping. A26 also has roles in the attachment of MVs to the cell surface and incorporation of MVs into proteinaceous A-type inclusions in some orthopoxvirus species. However, A26 lacks a transmembrane domain, and nothing is known regarding how it associates with the MV, regulates incorporation of the MV into inclusions, and possibly prevents EV formation. Here, we provide evidence that A26 forms a disulfide-bonded complex with A27 that is anchored to the MV through a noncovalent interaction with the A17 transmembrane protein. In the absence of A27, A26 was unstable, and only small amounts were detected. The interaction of A26 with A27 depended on a C-terminal segment of A26 with 45% amino acid identity to A27. Deletion of A26 failed to enhance EV formation by vaccinia virus, as had been predicted. Nevertheless, the interaction of A26 and A27 may have functional significance, since each is thought to mediate binding to cells through interaction with laminin and heparan sulfate, respectively. We also found that A26 formed a noncovalent complex with A25, a truncated form of the cowpox virus A-type inclusion matrix protein. The latter association suggests a mechanism for incorporation of virions into A-type inclusions in other orthopoxvirus strains.